Pemikiran Pendidikan Islam Moderat: Analisis Perspektif K.H. Yasin Asymuni – Analisis Konseptual Dan Implementasi - Moh Saifulloh Ma'sum; Muhammad Rofiq (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
This study discusses the concept of moderate Islamic education from the perspective of KH Yasin Asymuni, focusing on conceptual analysis and its implementation in the Islamic education system. The study aims to identify the key principles of moderate Islamic education developed by KH Yasin Asymuni and examine the application of these concepts in various Islamic educational institutions. The research method used is a qualitative literature study, analyzing various primary and secondary sources related to his thoughts. The findings indicate that KH Yasin Asymuni’s ideas emphasize a balance between religious and general sciences, the formation of an inclusive and tolerant Islamic character, and the application of contextual learning methods relevant to contemporary developments. His concept of moderate Islamic education not only focuses on the academic aspect but also instills national and humanitarian values within the education system. Therefore, KH Yasin Asymuni’s thoughts can serve as a foundation for developing a more adaptive and contextual Islamic education model in the modern era